Microbiome: a new era in normal and pathological changes skin studies - E. R. Araviiskaia; E. V. Sokolovskiy (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The paper contains review of studies on microbiota and cutaneous microbiome using modern techniques of methagenomic analysis. The existing data on microflora of normal skin and among the patients with acne, seborrhoeic dermatitis, rosacea atopic dermatitis are consequently analyzed. The interaction between microbiome and innate/adaptive immunity is presented The perspectives of knowledge on microbiome both in dermatology and cosmetology are pointed out.